Penile cancer in Ireland – A national review. Issue 3 (June 2022) - Anderson, S.; Breen, K.J.; Davis, N.F.; Deady, S.; Sweeney, P.
Abstract: Objective: Penile cancer is a rare malignancy, with a reported incidence of 1.5/100, 000 males in the Republic of Ireland in 2015. The aim of this study was to perform the first national review and to evaluate clinicopathological factors affecting survival. Subjects and methods: All cases of penile cancer in Ireland between 1995 and 2010 were identified through the National Cancer Registry Ireland (NCRI) and analysed to identify factors affecting survival. Results: 360 cases of penile cancer were identified, with a mean age at diagnosis of 65.5 years and 88% (n = 315) of cases occurred in those over 50. 91% (n = 328) of cases were squamous cell carcinomas (SCC). The majority of patients were treated surgically (n = 289), with 57% (n = 206) and 24% (n = 87) undergoing partial penectomy and total penectomy respectively. Only 18% (n = 65) received radiotherapy, and 8% (n = 27) received chemotherapy. Mean overall survival (OS) was 113 months, and five year disease specific survival (DSS) was 70% (95%CI: 59.1–77.8%). Age at diagnosis, nodal status and presence of metastatic disease were independent prognostic markers on multivariate analysis. Conclusion: This study represents the first national review of penile cancer in Ireland. The annual incidence and survival rates are comparable to European figures, though superior DSS has previously been reported from our institution, highlighting the role for centralisation of care in Ireland. Level of evidence: 2b. Highlights: Penile cancer is rare with an average of 24 cases per year in the Republic of Ireland. Surgery remains the mainstay of treatment. Age, nodal involvement, and presence of metastases are independent poor prognostic markers. Higher rates of organ preserving surgery are seen in countries where care has been centralised.